Growth and survival of giant gourami juvenile immerse indifferent frequencies using recombinant growth hormone - Syazili, Aras; Irmawati, .; Alimuddin, .; Sumantadinata, Komar (Jurnal Akuakultur Indonesia, 2012)
This study was aimed to determine the immersion frequency of recombinant growth hormone (rGH) in the growth stimulation of giant gourami juvenile. A total of 50 larvae at second day after first feeding, was immersed in 30 ppt salt water for 2 minutes, and then transferred into 200 mL of 9 ppt salt water containing 30 mg/L rGH in inclusion bodies form. Immersion was performed for 60 minutes and repeated once a week for two, three, four, and five weeks. As the control, fish was immersed with inclusion bodies without rGH (control-1), bovine serum albumin (control-2), 9ppt saline water without rGH (control-3) and in freshwater (control-4). Fish were kept in 7L aquaria during the first four weeks, transferred into 50L aquaria for two weeks, and then in hapa (2×1×1 m3 in size) for two weeks. The results showed that the highest (p<0.05) average body weight of giant gourami juvenile (2.23±0.19 g) was obtained at four times (four weeks) immersion treatment. Similar body weight of fish in two times (1.72±0.29 g), three times (1.68±0.34 g), and five times (1.81±0.17 g) immersion was obtained. Fish body weight of all controls was lower than the rGH-immersed fish. Average body weight of four time rGH-immersed fish (4.01 g) remained higher than other treatment and control (1.96 to 2.36 g) on 8th week of fish rearing. Survival of four times (96.67±1.15%), and five times rGH-immersion fish (95.33±4.16%) was similar, and higher than other treatments and controls (77.33 to 89.33%). Thus, higher growth rate and survival of giant gourami juvenile could be achieved by four times rGH immersion. Keywords: recombinant protein, growth hormone, immersion frequency, giant gourami